2015
DOI: 10.4103/0970-9290.159143
|View full text |Cite
|
Sign up to set email alerts
|

Does the bracket composition material influence initial biofilm formation?

Abstract: The in situ model tested was found to be effective in evaluating the accumulation and development of biofilm on orthodontic brackets. In the quantitative analysis, composite brackets showed greater biofilm adhesion values while metallic and ceramic presented similar biofilm absorbance spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…The material substratum is an essential factor that contributes to the ability of a pathogen to adhere to and form biofilm on a surface (Brandao et al . ; Fernandez‐Delgado et al . ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The material substratum is an essential factor that contributes to the ability of a pathogen to adhere to and form biofilm on a surface (Brandao et al . ; Fernandez‐Delgado et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…Our finding of high biofilm formation on polycarbonate is consistent with the finding of Brandao et al . () who demonstrated that polycarbonate composite orthodontic brackets sustained the highest level of bacterial adhesion in the buccal cavity compared to metal and ceramic brackets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences between metal and ceramic brackets have been studied in multiple aspects comparing different characteristics between the two types 6. Regarding plaque accumulation, some studies have proved no significance between both brackets,7 while Brusca et al8 reported the metal brackets have less bacterial accumulation compared to ceramic brackets.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies also reported that residue accumulation is commonly observed in the clinical scenario during orthodontic therapy with different types of devices (24)(25)(26)(27). In orthodontic patients, caries prevention represents a significant challenge (27) and requires clinical studies in order to prevent and control caries during orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%